The 'legal pluriverse' surrounding multinational military operations - Geiss, Robin; Krieger, Heike (Oxford : Oxford University Press, 2020)
This text conceptualizes and examines theories of the 'Legal Pluriverse': the multiplicity of rules that regulate multinational missions and the diverse actors involved. The text sets out the various legal regimes, assesses how these rules interact, and exposes norm conflicts, areas of legal uncertainty, or ambiguous loopholes.
This edition previously issued in print: 2019.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on January 14, 2020).
Keywords: Intervention (International law); Multinational armed forces; Law; International law